Kobiety-matki w wybranych tekstach publicystycznych Elizy Orzeszkowej - Jaśkiewicz, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
This article presents women-mothers in selected journalistic texts of Eliza Orzeszkowa, the most outstanding female Polish writer of the positivism period. At that time the issue of the role of women in the society became very popular. There were a lot of politics and writers, who wanted to guarantee women a real freedom and to make them really equal with men. According to their opinion, women should have a right to study at universities and to perform any profession they wanted. What is more, people noticed that women had one especially very important role – they had to be good mothers, so that they could bring up their children properly. Although Eliza Orzeszkowa has never become a mother, she took a keen interest in all issues connected with families. She has been even called a tutor of the Polish people. Besides, her experience from the childhood had a strong impact on her mature writing. Orzeszkowa’s mother was not a perfect one, so she did not have a strong relationship with her daughter. Women-mothers in novels of Orzeszkowa, similar to the writer’s mother was described as “elegant mothers”. What is more, Orzeszkowa was aware of the fact that in 19th century, when a situation in Poland after January Uprising was especially difficult, women had to cope with many problems. What is the most important, they had to work to earn their children’s living. In fact, women were not prepared for any job, because their education was rather poor. That is why Eliza Orzeszkowa made family’s matters the main topic of her literary output. She has written about upbringing and education of young women not only in her novels, but also in her journalistic texts. Kilka słów o kobietach is probably the most famous one, but Orzeszkowa has written also many other articles connected with those issues. The main aim of this article is to present some of them, which are probably the most important ones.